Compromised oxygen uptake in speed skaters during treadmill in-line skating - Rundell, K. W. (Medicine & Science in Sports & Exercise, 1996)
The "sitting" posture of speed skating may result in compromised blood flow to the working muscles, thus limiting oxygen uptake. To examine this metabolic problem, male (N = 7) short track speed skaters performed running (TR), in-line skating upright (US), and in-line skating in the "sitting" position (LS) on a motor driven treadmill on randomized days. Each test consisted of four 4-min stages at 2.24, 2.68, 3.13, and 3.58 m.s-1 (5, 6, 7, and 8 mph) at 5% incline. After a brief rest, athletes performed at 4.03 m.s-1 (9 mph) with elevation increasing 1% each minute to exhaustion. Two on-ice 1000-m time trials (TT) were performed to assess the relationship between performance and laboratory measurements. Peak VO2 was lower during LS (57.2 +/- 2.7, 62.3 +/- 4.0, and 64.3 +/- 1.6; for LS, US, and TR, respectively; P < 0.05). At equivalent speeds, submaximal O2 uptake was lower for LS and blood lactate was higher (P < 0.05). LS peak VO2 (ml.kg-1.min-1) was strongly related to TT (P < 0.05). The depressed VO2 and higher blood lactate during LS may be related to decreased knee or trunk angle. Peak VO2 values during skating did not approach values during running. Evaluation of speed skaters in a sports-specific test is congruent with performance and demonstrates potential in addressing the unique physiological demands of the sport.